BERBICARA AUTOETNOGRAFI: METODE REFLEKTIF DALAM PENELITIAN ILMU SOSIAL - Anne Shakka (Lensa Budaya: Jurnal Ilmiah Ilmu-Ilmu Budaya, 2019)
The research method using autoetnography is a research method that is still fairly new to be used in social research, especially in Indonesia. There are still many debates and criticisms aimed at this method, among others are very high subjectivity, problems regarding the code of ethics in research, lack of analysis, and researchers do not need to go to the field as in usual research. This paper is an argument about the method of autoetnography as an academic, valid, and analytical research method in social research, especially in cultural studies.  Keywords: Autoethnography, Research Method